PTH-032 A study of the yield of investigation in recurrent iron deficiency anaemia. (June 2019) - John, Christopher; Whiller, Nicola; Smith, Carla; Snook, Jonathan; Ayres, Lachlan
Abstract : Introduction: Recurrent iron deficiency anaemia (IDA) is a relatively common clinical condition, with potentially serious gastro-intestinal (GI) causes. Previous studies have shown that 9.6–25% of patients with negative initial upper and lower GI investigations go on to develop recurrent IDA, with up to 55% of these patients being diagnosed with a GI pathology. 1 2 There are well established guidelines on initial investigation, but there are few data on the yield of reinvestigation for recurrent IDA. The aim of this study was to determine the diagnostic yield from investigating recurrent IDA, using a larger dataset than the few previous smaller studies. Methods: The electronic patient records of the prospectively maintained IDA database at Poole Hospital NHS Foundation Trust were retrospectively examined. Patients were categorised as recurrent IDA if they re-presented a year or more after their initial investigation. Data were collected on index and repeat endoscopic and/or radiological investigations and any supplementary small bowel investigations. Results: 693 patients with IDA were included from January 2016 to September 2017. 86 patients had recurrent IDA. Of those with recurrent IDA, a cause was found in 20 patients (23%), including 4 malignancies (4.6% of all recurrent IDA), 3 cases of Crohn's disease, along with vascular lesions and Upper GI ulceration. For all patients with recurrent IDA and those in whom a cause was identified mean age was 67.6 years and 59.9 years respectively; the mean interval between presentations was 5.5 years (range: 1.1–15.1) and 5.7 years (range: 1.8–13) respectively (NS). There was no significant difference between the haemoglobin levels of patients with a cause found (97 g/L) compared patient where no cause was found (99.1 g/L). In those with recurrent IDA 11/86 (12.8%) of patients had causative pathology identified on repeat routine upper and lower GI investigation, 9/86 (10.5%) had a cause identified following small bowel investigation. The yield of small bowel investigation was 30% in recurrent IDA Conclusions: A significant proportion of patients have GI pathology on re-investigation of recurrent IDA, including malignancy in 4.6%. We suggest recurrent IDA is re-investigated with bi-directional endoscopy initially, with consideration of small bowel investigation. References: Soon A, Cohen BL, Groessl EJ, et al. Long-Term Outcomes and Prognostic Factors for Patients with Endoscopy-Negative Iron Deficiency Dig Dis Sci 2013;58:488. McLoughlin MT, Tham TC. Long-term follow-up of patients with iron deficiency anaemia after a negative gastrointestinal evaluation. Eur J Gastroenterol Hepatol 2009;21:872–876.